Effect of NaOH Treatment on Properties of Phoenix Sp. Fiber. Issue 6 (1st November 2016) - Rajeshkumar, G.; Hariharan, V.; Scalici, T.
ABSTRACT: The aim of this paper is to investigate the effect of an alkali treatment on physical, chemical, mechanical, and morphological properties of Phoenix Sp . fibers. The use of natural fibers as reinforcement in polymer composites requires a deep investigation to understand their behavior and which treatment is more appropriate to improve the quality of the untreated material. For this reason, fibers were extracted from the petioles of the Phoenix Sp . plant and they were treated with NaOH solution in different weight concentrations (5%, 10%, and 15%). The mechanical behavior was investigated through tensile test on single fiber at different gauge length (20 mm, 30 mm, 40 mm, 50 mm, and 60 mm). Chemical and physical analysis were performed to define the material properties. In particular, density analysis of untreated and treated fibers, optical analysis to measure the diameter of the fibers, moisture content evaluation, and a chemical composition analysis were carried out through standard methods. The modification of the surface morphology due to the alkali treatment was analyzed through scanning electron microscope analysis.